Nutritional Composition of Strobilanthes Crispus Juice and its Effects on Hyperglycaemia, Hyperlipidemia, Wound Healing and Toxicity in Rats - Noor Azmi, Norfarizan Hanoon (2009)
Strobilanthes crispus juice is reported to have good medicinal properties for treating diabetes mellitus and wound healing. The first part of this study evaluated the effect of S. crispus juice on hyperglycaemic, hyperlipidemic and antioxidant enzymes in normal and STZ-induced hyperglycaemic male and female rats at dosages of 140, 210 and 280 mg/kg of body weight (bw) for 30 days. Serum glucose, lipid profile (total cholesterol, triglyceride, HDL-cholesterol, LDL-cholesterol), antioxidant enzymes (glutathione peroxidase and superoxide dismutase) were determined on day 0, day 15 and day 30. The result showed that significant decrease of serum glucose levels in male and female diabetic rats with treated glibenclamide and all groups treated with 140, 210 and 280 mg/kg bw of S. crispus juice on days 15 and 30 when compared to control group and baseline data (zero day). The highest reduction of glucose level was 80.9 % on day 30 in male diabetic group treated with 280 mg/kg bw S. crispus juice, followed by 78.9 % reduction in group treated with 210 mg/kg bw, and 67.4 % reduction in group treated with 140 mg/kg bw of S. crispus juice. In female diabetic groups, reduction of glucose level was 78.2 %, 68.9 % and 68.6 % in groups treated with 140, 210 and 280 mg/kg bw of S. crispus juice respectively. Administration of S. crispus juice also reduced total cholesterol, triglyceride, LDLcholesterol; increased HDL-cholesterol, the activity of glutathione peroxidase and superoxide dismutase in STZ-induced diabetic and normal rats. Second part of this study was to determine the effect of S. crispus juice on wound healing and antioxidant enzymes (glutathione peroxidase and superoxide dismutase) in normal and diabetic rats. Three levels of dosage (70, 100 and 140 mg/kg of body weight) were orally and repeatedly administered for 7 days. Mid-dorsal linear incisions of 2 cm in length were made on each animal. The results showed that supplementation of S. crispus juice enhances wound closure in normal and diabetic rats. Glutathione peroxidase and superoxide dismutase were increased in diabetic group treated with S. crispus juice. Third part of this study investigated the proximate composition, vitamin and mineral contents of Strobilanthes crispus juice. The proximate analysis showed that S. crispus juice contained high moisture (75.01 %), carbohydrate content (33.47 %) and dietary fibre (12.29 g/100g). The contents of vitamin A, C and E in S. crispus juice were found to be 2.32 mg/100g, 9.37 mg/100g and 5.89 mg/100g respectively. S. crispus juice was found high in minerals including, sodium (37.21 mg/100g), potassium (124.99 mg/100g), calcium (172.88 mg/100g), ferum (0.57 mg/100g), phosphorus (8.18 mg/100g), magnesium (27.86 mg/100g), copper (0.14 mg/100g) and zinc (1.49 mg/100g). The fourth part of this study evaluated the acute toxicity of S.crispus juice. The LD50 was determined with four different dosages of S. crispus juice (700, 2100, 3500 and 4900 mg/kg of body weight) administered orally to normal female and male rats. The rats were treated with a single dose of juice and toxic effects were observed within 7 days. The results showed that no death or toxicity signs were observed in LD50 tested in normal rats. In the blood chemistry tests, no significant changes (p<0.05) were observed for most parameters (aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, creatinine and albumin) tested in normal rats. The 30 days toxicity effect were determined by the repeated dosing study using normal and streptozotocin-induced diabetic rats of both sexes. Three level of dosage (140, 210 and 280 mg/kg of body weight) were orally and repeatedly administered for 30 days. The results showed that no significant changes in general behaviour, body weight and organ weight. No differences were noted between the test and control groups in haematological, macroscopic and histopathological findings. The administration of S. crispus juice to normal rats revealed insignificant change in liver and kidney functions, but significant reduction of aspartate aminotransferase (group female and male rats with administration 280 mg/kg b.w. of S. crispus juice), alanine aminotransferase (group female rats with 280 mg/kg b.w. of S. crispus juice) and alkaline phosphatase (group female rats with 210 mg/kg b.w. of S. crispus juice). In streptozotocin-induced diabetes, the rise in blood glucose is accompanied by an increase in serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and creatinine. After the administration of diabetic rats with S. crispus juice for 30 days, there was a significant reduction in AST, ALT, ALP and creatinine. In conclusion, S. crispus juice has high nutritional value and found non-toxic. It shows potential as an antidiabetic drink and additional nutraceutical supplement for wound healing for diabetic patients.